Policy on the Development of Doctor's Functional Officials in the State Civil Apparatus Against Violation of the Doctor's Code of Ethics - Apriyanto Apriyanto (Fakultas Hukum Universitas Lampung, 2020)
A doctor of the State Civil Apparatus (ASN) in the implementation of medical practice has the potential to be subject to ethical sanctions by his professional organization in the form of a recommendation to revoke the Practice License which causes loss of authority to practice. Based on this, the loss of authority will at least raise the question of whether losing the authority to carry out the medical profession will have implications for his functional position as an ASN doctor and what is the coaching policy as an ASN doctor functional official in relation to violations of doctor ethics. The research was conducted with a statue approach and a case approach. The result of the research is that the loss of formal authority due to ethical violations does not have implications for the functional position of doctors and the guidance carried out by ASN doctors who have been sanctioned for ethical violations in the form of re-competency tests, transfers, and dismissals. Suggestions are needed by laws and regulations that explain the stipulative meaning of the relationship between ethical violations and the application of disciplinary sanctions to make it easier for ASN doctors who are sanctioned by violations of the Code of Ethics